Family systems nursing conversations: influences on families with stroke - Susanna Pusa; Britt-Inger Saveman; Karin Sundin (BMC, 2022)
Abstract Background Since a family member's stroke affects the entire family, family systems nursing conversations (FSNCs) may be an appropriate intervention to support the family as a whole. The purpose of our study was to illuminate family members' experiences within their family situations 6 months after participating in FSNCs when a family member under 65 years of age had suffered a stroke. Methods Fourteen semi-structured follow-up interviews were conducted with family members 6 months after they had completed a series of 3 FSNCs. The interview transcripts were subjected to qualitative content analysis. Results Family members experienced that the FSNCs had contributed to greater understanding of each other and greater closeness in the family. The FSNCs had also facilitated a mutual understanding of the family's situation, which they could better manage and move forward with together. Conclusions FSNCs can support relational aspects and healthy transitions within families. However, long-term follow-up research is needed to generate sound evidence and inform education about FSNCs, as well as to facilitate their implementation. As a result, families may become better able to prevent the negative outcomes of illness in the family.